Clinical Significance of an m6A Reader Gene, IGF2BP2, in Head and Neck Squamous Cell Carcinoma - Deng, Xiaoli; Jiang, Qingshan; Liu, Zhifeng; Chen, Wen (Frontiers in Molecular Biosciences, 2020)
The importance of N6-methyladenosine (m6A) in tumor recurrence and prognosis has been recognized in recent years. The role of m6A readers, such as insulin-like growth factor 2 mRNA-binding protein 2 (IGF2BP2), in regulating head and neck squamous cell carcinoma (HNSCC) remains unclear. We, therefore, assessed the prognostic role of IGF2BP2 in HNSCC using openly available data from The Cancer Genome Atlas (TCGA) in conjunction with HNSCC patient sample immunohistochemistry (n = 36). The correlation between IGF2BP2 expression and clinical characteristics was then examined. The role of IGF2BP2 in prognosis was assessed by Kaplan–Meier curves and Cox analysis. Finally, TCGA data was used to explore possible carcinogenic mechanisms with multi-GSEA (gene set enrichment analysis). Analysis of TCGA data and IHC results revealed that IGF2BP2 was upregulated in HNSCC tumor tissues, and the expression level was related to the T stage. Simultaneously, Kaplan–Meier curves and Cox analysis indicated that highly expressed IGF2BP2 correlated with poor prognosis and that IGF2BP2 was a potential prognostic factor for HNSCC. Gene set enrichment analysis revealed that scavenging and degradation, synthesis and metabolism, cell growth, death and motility, and cancer pathways were differentially enriched in patients with high IGF2BP2 expression. Our results demonstrate that IGF2BP2 plays an important role in tumor progression and may serve as an important biological prognostic factor for HNSCC.